2016
DOI: 10.1053/j.seminhematol.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched unrelated donor transplantation

Abstract: There are now over 25 million volunteer donors registered worldwide for patients in need of a life-saving hematopoietic cell transplant to cure blood disorders. Although an HLA-matched donor remains the preferred stem cell source for transplantation, the use of a donor with limited HLA mismatching may be considered. Significant advances in clinical and basic research have been instrumental in furthering the understanding of donor-recipient HLA mismatches that are better tolerated than other mismatches. An incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Human leukocyte antigen (HLA) matching between recipients and donors is a prerequisite for successful allogeneic hematopoietic stem cell transplantation (HSCT), notably to avoid graft versus host disease (GVHD) as main posttransplant complication. Although new protocols for selecting donors are increasingly sought, even across the histocompatibility barrier [1][2][3], the gold standard is to look first for an HLA identical sibling. If such a genotypically identical sibling cannot be found, the preferred alternative is to search for a 10/10 or 12/12 phenotypically matched unrelated donor (MUD) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA) matching between recipients and donors is a prerequisite for successful allogeneic hematopoietic stem cell transplantation (HSCT), notably to avoid graft versus host disease (GVHD) as main posttransplant complication. Although new protocols for selecting donors are increasingly sought, even across the histocompatibility barrier [1][2][3], the gold standard is to look first for an HLA identical sibling. If such a genotypically identical sibling cannot be found, the preferred alternative is to search for a 10/10 or 12/12 phenotypically matched unrelated donor (MUD) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…HLA genes are inherited within parental haplotypes that represent groups of physically linked alleles with possible conserved association because of positive "linkage disequilibrium" [32]. By definition, "HLA haploidentical transplant" means the familiar donor and recipient share only 1 inherited HLA haplotype, whereas the second is different and randomly derived.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, from the patient's perspective the presence of donor disparity not shared by the recipient provokes the HVG alloresponse that increases the risk of graft failure. Thus, in the case of homozygosis of some HLA loci, reduced HLA disparity may involve only 1 vector of the allo-immune response; this may affect GVH allo-response in the case of homozygosis of the recipient or HVG allo-response in the case of homozygosis of the donor [32].…”
Section: Introductionmentioning
confidence: 99%
“…23,[27][28][29][30] There is currently a consensus that a single HLA MM at the HLA-A, -B, -C, and -DRB1 loci is clinically relevant; however, which of these loci is the most important one has not been agreed upon. 20,31,32 Different studies reported various results, for example, Petersdorf et al reported that mortality and GvHD increase with increasing numbers of HLA MMs as well as that a single HLA-B MM increased grade III-IV aGvHD incidence. 33 Ayuk et al reported that an increasing HLA disparity was associated with a lower OS and DFS for patients with a 9/10 and ≤8/10 MUD compared with the patients with a 10/10 MUD.…”
Section: Discussionmentioning
confidence: 99%